Inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4) in saliva of pigs: evaluation of two commercially available ELISA kits for its measurement and distribution of its main components - Alba Ortín-Bustillo; Silvia Martínez-Subiela; José Joaquín Cerón; Antonio González-Bulnes; Asta Tvarijonaviciute; Alberto Muñoz-Prieto (PLoS ONE, 2025)
Inter-alpha-trypsin inhibitor protein heavy chain 4 (ITIH4), also named porcine major acute phase protein (Pig-MAP), is a positive acute phase protein (APP) in pigs and can be measured in plasma and also in saliva to assess the animal health. The objectives of this report were (1) to evaluate if different commercially available porcine ELISA kits can measure ITIH4 concentrations in saliva samples of pigs, and (2) to study the distribution of ITIH4 components in saliva and compare it to the distribution in plasma. The results showed that two of the ELISA kits used in this report could measure salivary ITIH4 with precision and accuracy, but only one showed significant differences between pigs with tail biting and control animals without this condition. Western blotting analysis revealed the presence of a different distribution of ITIH4 bands in saliva samples compared to plasma samples. In conclusion, in saliva of pigs ITIH4 can be quantified using a commercial ELISA kit increasing its concentration in cases of tail biting. In addition, ITIH4 shows bands at western blot in saliva that are different from serum but are compatible with different ITIH4 forms. These data confirm that ITIH4 can be detected in saliva and be potentially used as a biomarker of inflammation.